Regular measures and normal lattices - Carmen Vlad (International Journal of Mathematics and Mathematical Sciences)
In this paper, we investigate M(ℒ) in case ℒ is a normal lattice of subsets of X and we extend the results to ℒ1, ℒ2-lattices of subsets of X, such that ℒ1⊂ℒ2 and ℒ1 separates ℒ2. We define the outer measures μ′ and μ″ which prove very useful in proving some of the above results.